Dextran-coated iron oxide nanoparticle-improved therapeutic effects of human mesenchymal stem cells in a mouse model of Parkinson's disease. Issue 6 (26th January 2018) - Chung, Tsai-Hua; Hsu, Szu-Chun; Wu, Shu-Hui; Hsiao, Jong-Kai; Lin, Chih-Peng; Yao, Ming; Huang, Dong-Ming
Abstract : Dex-IO NPs can improve the therapeutic benefit of hMSCs in a PD mouse model. Abstract : Parkinson's disease (PD) is a prevalent neurodegenerative disease characterized by the loss of dopaminergic (DA) neurons. With their migration capacity toward the sites of diseased DA neurons in the PD brain, mesenchymal stem cells (MSCs) have the potential to differentiate to DA neurons for the replacement of damaged neurons and to secrete neurotrophic factors for the protection and regeneration of diseased DA neurons; therefore MSCs show promise for the treatment of PD. In this study, for the first time, we demonstrate that dextran-coated iron oxide nanoparticles (Dex-IO NPs) can improve the therapeutic efficacy of human MSCs (hMSCs) in a mouse model of PD induced by a local injection of 6-hydroxydopamine (6-OHDA). In situ examinations not only show that Dex-IO NPs can improve the rescue effect of hMSCs on the loss of host DA neurons but also demonstrate that Dex-IO NPs can promote the migration capacity of hMSCs toward lesioned DA neurons and induce the differentiation of hMSCs to DA-like neurons at the diseased sites. We prove that in vitro Dex-IO NPs can enhance the migration of hMSCs toward 6-OHDA-damaged SH-SY5Y-derived DA-like cells, induce hMSCs to differentiate to DA-like neurons in the conditioned media derived from 6-OHDA-damaged SH-SY5Y-derived DA-like cells and promote the protection/regeneration effects of hMSCs on 6-OHDA-damaged SH-SY5Y-derived DA-like cells. We confirm the potential of MSCs for cell-based therapy for PD. Dex-IO NPs can be used as a tool to accelerate and optimize MSC therapeutics for PD applicable clinically.